Answer

Verified

382.2k+ views

**Hint:**We first need to rearrange the given equation in the standard form of quadratic equation. That is in the form of \[a{x^2} + bx + c = 0\]. After that we can solve this using various methods that are by completing the square, factorization, graph or by quadratic formula. Here we need to use a quadratic formula that is \[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\].

**Complete step-by-step solution:**

Given, \[7{x^2} - 5 = 2x + 9{x^2}\]

Shifting the terms we have,

\[2x + 9{x^2} - 7{x^2} + 5 = 0\]

\[2{x^2} - 2x + 5 = 0\]

Since the degree of the equation is 2, we have 2 factors or two roots.

On comparing the given equation with the standard quadratic equation\[a{x^2} + bx + c = 0\], we have\[a = 2\], \[b = - 2\] and \[c = 5\].

Now we use quadratic formula or Sridhar’s formula,

\[x = \dfrac{{ - b \pm \sqrt {{b^2} - 4ac} }}{{2a}}\].

Substituting we have,

\[ \Rightarrow x = \dfrac{{ - ( - 2) \pm \sqrt {{{\left( { - 2} \right)}^2} - 4(2)(5)} }}{{2(2)}}\]

\[ = \dfrac{{2 \pm \sqrt {4 - 40} }}{4}\]

\[ = \dfrac{{2 \pm \sqrt { - 36} }}{4}\]

\[ = \dfrac{{2 \pm \sqrt { - 1 \times 36} }}{4}\]

We know that \[\sqrt { - 1} = i\],

\[ = \dfrac{{2 \pm i\sqrt {36} }}{4}\]

We know that 36 is a perfect square,

\[ = \dfrac{{2 \pm 6i}}{4}\]

Taking 2 common,

\[ = \dfrac{{2(1 \pm 3i)}}{4}\]

\[ = \dfrac{{1 \pm 3i}}{2}\]

Thus we have two roots,

\[ \Rightarrow x = \dfrac{{1 + 3i}}{2}\] and \[x = \dfrac{{1 - 3i}}{2}\]. This is the required answer.

**Note:**Since we have a polynomial of degree two and hence it is called quadratic polynomial. If we have a polynomial of degree ‘n’ then we have ‘n’ roots. In the given problem we have a degree that is equal to 2. Hence the number of roots are 2. Also we know that \[\sqrt { - 1} \] is undefined and we take \[\sqrt { - 1} = i\] that is an imaginary number. Quadratic formula and Sridhar’s formula are both the same. We know that the product of two negative numbers gives us a positive number. Also keep in mind when shifting values from one side of the equation to another side of the equation, always change sign from positive to negative and vice-versa.

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Give 10 examples for herbs , shrubs , climbers , creepers

Difference Between Plant Cell and Animal Cell

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Change the following sentences into negative and interrogative class 10 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

Select the word that is correctly spelled a Twelveth class 10 english CBSE